Coping with the COVID-19 pandemic: the technical, moral and facilitating role of management control. Issue 6 (20th May 2021) - Passetti, Emilio Emilio; Battaglia, Massimo; Bianchi, Lara; Annesi, Nora
Abstract : Purpose: The study analyses how management control supports the organisation's response to the COVID-19 pandemic lockdown. Design/methodology/approach: Video interviews with top and middle-level managers who were directly involved in handling the response to the COVID-19 crisis in late winter and spring 2020 form the empirical base. The object-of-control framework and the distinction between organic and mechanistic management controls inform the exploratory case analysis of a large food retail cooperative in Italy. Findings: Both organic and mechanistic management control mechanisms enabled an immediate response and management of the crisis. The use of cultural, action and results controls supported employees' health and safety coordination, a tight monitoring of financial performance and social interventions in support of the local community. Originality/value: The study provides original exploratory insights on the use and role of management control in the context of an unprecedented emergency and an unplanned setting (i.e. a pandemic crisis), which is an under-investigated topic in the accounting literature. The study shows how management control operated, linking moral and technical aspects as well as facilitating organisational adaptation and pandemic effects mitigation.